State anxiety of women basketball players prior to competition - Elgin, S. L.
The purpose of this study was to use the third version of the Mental Readiness Form (MRF-3) to examine the state anxiety levels of women basketball players prior to a scheduled competitive event. College women basketball players (N=34) from Midwestern colleges were asked to fill out the MRF-3 three hours before (pretest) and again thirty minutes before (posttest) a competitive event. The education level and starter status of each player was used to examine their effects on anxiety levels. A freshman starter was thought to have higher anxiety levels than a sophomore, junior, or senior. Inconsistent with the hypothesis, 4x2 and 2x2 mixed design Analysis of Variances indicated that education level and starter status had no effect on the anxiety levels. A 2x2 mixed design ANOVA indicated the significance of the main effect for starter status with respect to confidence levels (p< .05).